Callochiton Gray 1847 - Dell'Angelo, Bruno; Landau, Bernard M.; Sosso, Maurizio; Taviani, Marco (Zenodo, 2020)
Genus Callochiton Gray, 1847 Type species. Chiton laevis Montagu, 1803 ( non Pennant, 1777) = Callochiton septemvalvis (Montagu, 1803), by subsequent designation (Gray 1847). Distribution. Mostly tropical and subtropical regions of the Indo-Pacific (including Japan, absent from the northeastern Pacific). In the Atlantic Ocean, it is restricted to the sub-Antarctic and the eastern part further north. The fossil record extends back to the lower Oligocene of New Zealand (Ashby 1929), the Miocene of Europe (Bałuk 1984; Dell’Angelo et al. 2016), Argentina (Urteaga et al. 2011) and Australia (Ashby 1939) and the Pleistocene of Japan (Itoigawa et al . 1976). : Published as part of Dell'Angelo, Bruno, Landau, Bernard M., Sosso, Maurizio & Taviani, Marco, 2020, Late Pleistocene Red Sea Mollusca: 1. Polyplacophora, pp. 401-449 in Zootaxa 4772 (3) on page 409, DOI: 10.11646/zootaxa.4772.3.1, http://zenodo.org/record/3819654 : {"references": ["Gray, J. E. (1847) A list of the genera of Recent Mollusca, their synonyms and types. Proceedings of the Zoological Society of London, 15, 129 - 206. https: // doi. org / 10.1111 / j. 1469 - 7998.1847. tb 00164. x", "Montagu, G. (1803) Testacea Britannica or Natural History of British Shells, Marine, Land and Freshwater, Including the Most Minute, Systematically Arranged and Embellished with Figures. Vol. 1 & 2. White, London, xxxvii + 606 pp. 16 pls. [pp. i-xxxvii + 1 - 291 & pp. 292 - 606, pls. 1 - 16] https: // doi. org / 10.5962 / bhl. title. 33927", "Pennant, T. (1777) The British Zoology. 4. Crustacea, Mollusca, Testacea. Benjamin White, London, xviii + 156 pp., 193 pls.", "Ashby, E. (1929) New Zealand fossil Polyplacophora (chitons). Transactions and Proceedings of the New Zealand Institute, 60, 366 - 369, pl. 32.", "Baluk, W. (1984) Additional data on chitons and cuttlefish from the Korytnica clays (Middle Miocene; Holy Cross Mountains, Central Poland). Acta Geologica Polonica, 34, 281 - 297, pls. 1 - 17.", "Dell'Angelo, B., Giuntelli, P., Sosso, M. & Zunino, M. (2016) Polyplacophora from the Miocene of North Italy. Part 2: Callochitonidae, Chitonidae, Lepidochitonidae, Acanthochitonidae and Cryptoplacidae. Rivista Italiana di Paleontologia e Stratigrafia, 122, 23 - 54.", "Urteaga, D., Griffin, M. & Pastorino, G. (2011) Callochiton monteleonensis n. sp., first record of Polyplacophora (Mollusca) from the Neogene of Argentina. Journal of Paleontology, 85, 1181 - 1187. https: // doi. org / 10.1666 / 11 - 041.1", "Itoigawa, J., Kuroda, M., Naruse, A. & Nishimoto, H. (1976) Polyplacophora assemblages from the Pleistocene formations of Boso and Miura Peninsulas, environs of Tokyo, Japan. Bulletin of the Mizunami Fossil Museum, 3, 171 - 204."]}